Oxygen saturations and neurodevelopmental outcomes in single ventricle heart disease. Issue 6 (28th March 2019) - Wolfe, Kelly R.; Brinton, John; Di Maria, Michael V.; Meier, Maxene; Liptzin, Deborah R.
Abstract: Objectives: To evaluate whether the degree of hypoxemia following stage‐I and stage‐II palliative surgeries predicts neurodevelopmental outcomes at 14 months of age in children with single ventricle congenital heart disease (SVCHD). Design: We analyzed longitudinal data from two Pediatric Heart Network (PHN) randomized controlled trials, with a total of 328 subjects. Oxygen saturations, measured via pulse oximetry, at time of discharge from stage‐I and stage‐II surgeries were the primary predictors of interest, and Bayley Scales of Infant Development‐II (BSID‐II) scores at 14 months old were the primary outcome measure. Relevant covariates from previously‐published PHN studies were also included in regression models. Results: Oxygen saturations at time of discharge from stage‐I and stage‐II surgeries were not related to BSID‐II scores. Having one or more oxygen saturation measurements below 80% was also not associated with BSID‐II scores, and neither was change in oxygen saturations over time. These relationships were not altered by inclusion of relevant covariates. Conclusions: In this large cohort of children with SVCHD, oxygen saturations post‐stage‐I and post‐stage‐II palliation surgeries as measured via pulse oximetry were not associated with neurodevelopmental outcomes at 14 months of age. The relationship between oxygen saturations and neurodevelopment in SVCHD is likely complex, and neurodevelopment is known to be affected by a number of factors. Pulse oximetry may also be an insufficient proxy for cerebral oxygen delivery. Clinically, pulse oximetry readings during the interstage and post‐stage‐II surgery periods are not a reliable predictor of future neurodevelopmental risk.